2022
DOI: 10.1177/00380261221079115
|View full text |Cite
|
Sign up to set email alerts
|

Pluriversal intersectionality, critique and utopia

Abstract: Since intersectionality theory constitutes a critical assessment of the way the social world operates and strives for social justice, it entails an image of how the world is and how things could become. In this article a version of intersectionality with particularly strong counter-cultural tendencies is considered. Drawing on Ruth Levitas’s approach to utopia as ‘method’, it makes explicit pluriversal intersectionality’s utopian content. It is shown that the defining features of this intersectionality theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Many international experts agreed that intersectionality is an open-ended approach that is generative, and users can creatively interpret its scope to adapt its premise. The unfolding and evolution of its applications continues as it propagates knowledge production (Collins et al, 2021;Gemignani & Hernández-Albújar, 2019;Hankivsky, 2014;Masquelier, 2022;UN Women, 2021). Organizations, individual practitioners, researchers, educators, policy and law makers, and social justice experts can address intersectionality issues in their policies, programs, and curricula designs to work toward an equitable future by using it.…”
Section: Relational Ethics and Intersectionality: A Side-by-side Comp...mentioning
confidence: 99%
“…Many international experts agreed that intersectionality is an open-ended approach that is generative, and users can creatively interpret its scope to adapt its premise. The unfolding and evolution of its applications continues as it propagates knowledge production (Collins et al, 2021;Gemignani & Hernández-Albújar, 2019;Hankivsky, 2014;Masquelier, 2022;UN Women, 2021). Organizations, individual practitioners, researchers, educators, policy and law makers, and social justice experts can address intersectionality issues in their policies, programs, and curricula designs to work toward an equitable future by using it.…”
Section: Relational Ethics and Intersectionality: A Side-by-side Comp...mentioning
confidence: 99%
“…In other words, we intuitively know that intersecting systems of power influence and shape the privilege or discrimination individuals experience, and vice-versa. Masquelier (2022) argued that co-formation resonates with decolonial approaches and indigenous ways of thinking, which have always embraced the interconnectedness and interdependence of reality. They suggested that dialogue is crucial for emancipation and empowerment, enabling diverse people to organize collectively and to claim equity in cooperative terms.…”
Section: Intersectionality and Intersectional Data Sciencementioning
confidence: 99%
“…Nei suoi tre decenni di storia, l'intersezionalità si è andata a costituire come un chiaro strumento di critica sociale (Hill-Collins 2019) contenente un'immagine implicita di come le relazioni sociali potrebbero essere, una volta superata la "matrice del dominio" basata su discriminazioni di genere, razziali e di classe. L'intersezionalità inoltre, proprio per la sua valenza metodologica -come studio intra e inter-categorico delle rappresentazioni e dei rapporti sociali -se associata alla dimensione utopica, rappresenta l'aspirazione a connettere diverse forme di mobilitazione e critica sociale, valorizzando quindi versioni pluralistiche e multiculturali dell'utopia, pienamente capaci di riconoscere l'inter-esistenza di differenze (Masquelier 2021).…”
Section: Utopie Post-eurocentricheunclassified